2019
DOI: 10.5551/jat.44891
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators Across the Spectrum of Ankle-Brachial Index

Abstract: Aim: Peripheral artery disease (PAD) is a manifestation of atherosclerosis with poor prognosis. It is generally complicated by vascular calcification, which is located either in the intima as patchy infiltrates; or circumferentially in the media, also known as medial arterial calcification (MAC). Obstructive PAD is reflected by low anklebrachial index (ABI ≤ 0.9), whereas MAC is revealed by high ABI (ABI > 1.4). Considering the increase in cardiovascular mortality at both ends of the ABI spectrum, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…According to Avanzas et al [14], elevated serum NTP predicts future adverse cardiac events in patients with chronic stable angina pectoris. Furthermore, some studies demonstrated an association of NPT with the ankle-brachial index (ABI) and increased mortality of patients with vascular calcification or patients undergoing angiography [10,15,16]. Contrastingly, Shirai et al [6] reported that NPT level increased in coronary lesions and circulating blood in patients with CAD to counter inflammation and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to Avanzas et al [14], elevated serum NTP predicts future adverse cardiac events in patients with chronic stable angina pectoris. Furthermore, some studies demonstrated an association of NPT with the ankle-brachial index (ABI) and increased mortality of patients with vascular calcification or patients undergoing angiography [10,15,16]. Contrastingly, Shirai et al [6] reported that NPT level increased in coronary lesions and circulating blood in patients with CAD to counter inflammation and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Various other mechanisms associated with an abnormal ABI may contribute to CKD, further supporting our findings. Ozkaramanli Gur et al reported increased cytokine levels in both low and high ABI groups in patients with previous coronary artery bypass grafting 41) . Therefore, both low and high ABI groups may have vascular damage in the kidney via circulatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on plasma biomarkers and incident PAD are few. One longitudinal study links cystatin C and incident PAD (Yang et al 2017), whereas only cross-sectional studies show relations between N-BNP (Falkensammer et al 2015), copeptin (Ozkaramanli et al 2018), and PAD in patients with prevalent cardiovascular disease. In a cross-sectional study comparing male patients with IC to an age-and diabetes matched control group (Kollerits et al 2013), both MR-proADM and MR-proANP were associated with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Copeptin acts as a non-specific marker of acute illness and disease severity, and plasma concentrations are elevated in acute cardiac conditions, such as myocardial infarction (Mueller et al 2018). As elevated levels of copeptin are cross-sectionally associated with ankle-brachial index in a population with advanced coronary artery disease (Ozkaramanli et al 2018), suggesting a relationship with PAD, it was relevant to prospectively relate levels of this marker to incident clinically relevant PAD.…”
Section: Introductionmentioning
confidence: 99%